Normativity as fact and procedural realism: Some observations on the prologue and 1st lecture of Ch. M. Korsgaard’s The Sources of Normativity - Tredanaro, Emanuele (Studia Kantiana, 2023)
In this paper, we offer some observations on the mobilisation of categories and arguments that Christine Marion Korsgaard presents in her work The Sources of Normativity (SN). In particular, in the main thesis set out in the prologue, we will identify normativity as fact, a common thread for reading those philosophers of modernity, whose ethical-political theorisations are taken by Korsgaard, in the lecture part of SN, as illustrative references of two conceptions of normativity: the realist and the voluntarist. We thus propose to modulate Korsgaard’s interpretation, seeking to show some implications of her main thesis and notion of procedural realism, since the prologue and the first lecture of SN, generally underestimated by the interpreters.